An Experimental Study of the Cyclic Compression after Impact Behavior of CFRP Composites - Raffael Bogenfeld (MDPI AG, 2021)
The behavior of impact damaged composite laminates under cyclic load is crucial to achieve a damage tolerant design of composite structures. A sufficient residual strength has to be ensured throughout the entire structural service life. In this study, a set of 27 impacted coupon specimens is subjected to quasi-static and cyclic compression load. After long intervals without detectable damage growth, the specimens fail through the sudden lateral propagation of delamination and fiber kink bands within few load cycles. Ultrasonic inspections were used to reveal the damage size after certain cycle intervals. Through continuous dent depth measurements during the cyclic tests, the evolution of the dent visibility was monitored. These measurements revealed a relaxation of the indentation of up to 90% before ultimate failure occurs. Due to the distinct relaxation and the short growth interval before ultimate failure, this study confirms the no-growth design approach as the preferred method to account for the damage tolerance of stiffened, compression-loaded composite laminates.